The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1158/1538-7445.am2014-1006
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 1006: Structural peculiarities of flavonoids influence anti-angiogenic, cytotoxic and antioxidant effects: experimental and insilico analysis

Abstract: Structural diversity of flavonoids and biological activities has remained an important discourse in the mainstream of flavonoid research. In the present studies different class of flavonoids such as flavones, flavanones and flavanolols were evaluated for their antiangiogenic, cytotoxic and antioxidant activities. The anti-angiogenic activity was evaluated using in vivo chorioallantoic membrane model (CAM), antioxidant potential and kinetics of free radical scavenging activity was determined using DPPH (2, 2-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recently, Shan et al have found that PSPC relieves kidney damage by inhibiting NLRP3-induced inflammation [8]. In addition, various flavonoids have been shown to inhibit VEGFR2 expression and its downstream signaling in the pathological angiogenesis of tumors and diabetic retinopathy [17, 18]. Given our preliminary evidence showing that VEGFR2 stimulated ROS overproduction, the current study aims at investigating whether PSPC alleviates kidney injury by downregulating VEGFR2-mediated oxidation stress and inflammation and further explaining the pathological mechanism underlying kidney damage in HFD-treated mice.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Shan et al have found that PSPC relieves kidney damage by inhibiting NLRP3-induced inflammation [8]. In addition, various flavonoids have been shown to inhibit VEGFR2 expression and its downstream signaling in the pathological angiogenesis of tumors and diabetic retinopathy [17, 18]. Given our preliminary evidence showing that VEGFR2 stimulated ROS overproduction, the current study aims at investigating whether PSPC alleviates kidney injury by downregulating VEGFR2-mediated oxidation stress and inflammation and further explaining the pathological mechanism underlying kidney damage in HFD-treated mice.…”
Section: Introductionmentioning
confidence: 99%